Пошаговое объяснение:
2. 4(x+2)-12=x+6-2x
4x-4=6-x
5x=10
x=2
3.|x-5|=27
x=32
2)
домножаем обе части на 12, чтобы избавиться от дроби
4х + 8 - 12 - х + 6 + 2х = 0
5х + 2 = 0
5х = -2
х = -2/5 = -0,4
3) 6*(х - 5) = 162 при х - 5 >= 0
6x - 30 = 162
6x = 162 + 30
6x = 192
x = 192/6
x = 32
6*(-(х - 5)) = 162 при х - 5 < 0
6(-x + 5) = 162
-6x + 30 = 162
-6x = 162 - 30
-6x = 132
x = 132/(-6)
x = -22
x =
Пошаговое объяснение:
2. 4(x+2)-12=x+6-2x
4x-4=6-x
5x=10
x=2
3.|x-5|=27
x=32
Пошаговое объяснение:
2)
домножаем обе части на 12, чтобы избавиться от дроби
4х + 8 - 12 - х + 6 + 2х = 0
5х + 2 = 0
5х = -2
х = -2/5 = -0,4
3) 6*(х - 5) = 162 при х - 5 >= 0
6x - 30 = 162
6x = 162 + 30
6x = 192
x = 192/6
x = 32
6*(-(х - 5)) = 162 при х - 5 < 0
6(-x + 5) = 162
-6x + 30 = 162
-6x = 162 - 30
-6x = 132
x = 132/(-6)
x = -22
x =